The effect of online games on students’ mathematics learning outcomes at SMPN 1 Sintuk Toboh Gadang - Syahrial Syahrial (International Journal of Trends in Mathematics Education Research, 2022)
The purpose of this study was to see the significant effect of online games on students' mathematics learning outcomes at SMP N 1 Sintuk Toboh Gadang. The approach used in this study is a quantitative approach with the type of correlational research, namely research conducted between two or more variables that aims to find out whether there is a relationship and if there is, how close the relationship is and whether or not the relationship is meaningful. The instrument used in this study was a questionnaire or questionnaire and learning outcomes test used to determine the effect of online games on students' mathematics learning outcomes. The analysis used in this study was simple linear regression analysis. The results showed that: 1. The mathematics learning outcomes of grade VIII SMPN 1 Sintuk Toboh Gadang students who liked to play online games varied widely 2. There was an influence between playing online games on the mathematics learning outcomes of eighth grade students of SMPN 1 Sintuk Toboh Gadang, which was indicated by F count = 47, 85 F table = 4.6 this can also be seen from the regression coefficient value of -0.882. The simple linear regression equation obtained is Y = 184.41-0.6X where Y is the result of learning mathematics and X is the online games variable. The conclusion is that there is a negative effect of online games on students' mathematics learning outcomes in class VIII SMPN 1 Sintuk Toboh Gadang, both up and down and all independent variables (X) have an effect on the dependent variable (Y) of 77.7%.